Geographic enrolment of the top 100 in athletics running events from 1996 to 2012 - Marc, A.; Sedeaud, A.; Schipman, J.; Jacquemin, J. A.; Saulière, G.; Kryger, K. O.; Toussaint, J. F. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: It is widely accepted in the literature that athletes of West African origins achieve the best sprint performances, while athletes originating from East Africa are the most efficient at long distances. So far, no study has measured the evolution of these groups' contribution from 100 m to the marathon.